Human Capital as Experience Designers: Reframing Service Management in the F&B Industry: Lake Toba Tourism Ecosystem - Pratama Daryana, Aditiya; Angriani, Fenni (Journal of Research on Business and Tourism, 2025)
This study explores the transformation of human capital in the food and beverage (F&B) sector within Lake Toba's cultural tourism ecosystem. The research addresses a core issue: the limited role of F&B workers who are still viewed as mere service executors rather than experience designers. The study aims to reposition human resources as integral actors in delivering emotional and cultural value through tourism services. A qualitative approach was applied using thematic analysis, involving interviews, field observations, and document reviews across key destinations. Findings reveal five dominant themes: technical rigidity, lack of storytelling ability, absence of emotional labor, weak strategic awareness, and institutional training gaps. These insights led to the development of a six-stage conceptual model titled "Journey of Experience Design by F&B Human Capital," outlining the path from role awareness to reflective service delivery. The study concludes that transforming service roles in cultural destinations requires more than skill development; it necessitates cultural narrative training and emotional intelligence. Recommendations include localized training frameworks, stakeholder collaboration, and storytelling integration into F&B operations. This study contributes both theoretically and practically to the advancement of human-centered service innovation in heritage-based tourism.